Dynamics of development of hardiness as a factor in the formation of successful activity in the population future teachers – psychologists - Дюсембекова, Камила; Нагымжанова, Каракат (Pedagogy and Psychology, 2021)
The article presents a systematic theoretical analysis of the phenomenon of «hardiness». The main components of hardiness and their relationship are described. Features of formation of successful activity in the course of students, hardiness are defined. The influence of the components of hardiness on the formation of successful activity is characterized. The results of an empirical study of the level of hardiness of future teachers – psychologists are presented. On the basis of empirical data and literature analysis, the model «Dynamics of the development of hardiness in future teachers – psychologist» is built. Attempts are made to concretize the accumulated theoretical experience about the phenomenon of hardiness and its connection with successful activity. The results of measuring the dynamics of the development of hardiness in future teachers – psychologists and the impact on the formation of their successful activities are presented.